A bifunctional zero-dimensional organic-inorganic tin halide single crystal material with nonlinear optics and strong fluorescence emission and a preparation method and application thereof
Patent Information
- Application Number
- CN202611074092.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-30
AI Technical Summary
[0010]本发明的首要目的在于克服传统合成方法不环保、效率低、成本高等常规问题,以及锡基杂化材料难以理性构建非中心对称高性能NLO晶体、难以兼顾高效发光性能等技术瓶颈,提供一种新型的、兼具强二次谐波产生性能与优异光致发光特性的氮杂环卡宾-锡卤化物双功能光学晶体材料
[0029]1、晶体性能优异,兼具独特的双模态光学响应:
Smart Images

Figure CN123003597A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the fields of functional materials chemistry, crystal engineering, and nonlinear optics. Specifically, it relates to a zero-dimensional organic-inorganic hybrid tin halide bifunctional single-crystal material possessing both second-order nonlinear optical properties and strong fluorescence emission characteristics, and its green mechanochemical preparation method. Particularly, it relates to a non-centrosymmetric crystal [BMPIB]·SnCl6 synthesized using a nitrogen-containing heterocyclic carbene (NHC) derivative as an organic ligand via an efficient, solvent-free, or trace-solvent-based mechanochemical method. This material exhibits both significant second-harmonic generation response and stable intrinsic fluorescence emission performance. This invention also relates to the application of this bifunctional crystal in fields such as multi-mode optical anti-counterfeiting. Background Technology
[0002] Nonlinear optical (NLO) crystals are the cornerstone of modern photonics technology, enabling key functions such as laser frequency conversion (e.g., frequency doubling and sum-frequency generation), optical parametric amplification, and electro-optic modulation. They are widely used in laser technology, optical communication, precision spectroscopy, biological imaging, and information processing. Among these, second-order nonlinear optical processes, such as second harmonic generation (SHG), require materials with non-centrosymmetric crystal structures to produce non-zero second-order nonlinear polarizability (χ²). (2) Therefore, exploring and creating novel non-centrosymmetric NLO crystal materials has always been a core research direction in this field.
[0003] Traditional inorganic nonlinear optical crystals, such as barium β-borate (BBO), potassium titanium oxyphosphate (KTP), and potassium dihydrogen phosphate (KDP), while commercially available, still face numerous challenges: long crystal growth cycles, harsh conditions (high temperature and high pressure), high costs, poor machinability, and difficulties in flexibly controlling performance parameters such as optical band gap and nonlinear coefficient through chemical modification. Organic nonlinear optical crystals possess advantages such as high nonlinear coefficients and ease of molecular design, but generally suffer from low hardness, poor thermal stability, and low laser damage threshold.
[0004] In recent years, with the rapid development of information security, advanced anti-counterfeiting, and integrated optoelectronic devices, single functions (such as only possessing frequency doubling effect or only possessing single fluorescence emission) are no longer sufficient to meet the application requirements of high-density information encryption and multimodal optoelectronic devices. For example, in the field of advanced anti-counterfeiting, single fluorescence anti-counterfeiting is extremely easy to counterfeit, and is gradually evolving towards dual-modal multi-level anti-counterfeiting technology of "static fluorescence emission + dynamic nonlinear response (frequency doubling)". This creates an urgent need for the creation of dual-functional / multifunctional crystal materials that combine strong nonlinear optical effects with efficient photoluminescence (fluorescence) performance.
[0005] Organic-inorganic hybrid metal halide materials offer a novel solution to the aforementioned problems. These materials combine the structural diversity and high stability of inorganic components with the functional tunability and ease of processing of organic components. Their spatial symmetry, electronic structure, and optical response can be precisely controlled through molecular / crystal engineering. Tin (Sn)-based halides, in particular, have attracted widespread attention due to their environmental friendliness (low toxicity), rich coordination chemistry, and tunable wide bandgap properties. Furthermore, low-dimensional (e.g., zero-dimensional) hybrid tin halides, due to their strong exciton-phonon coupling effect, readily exhibit highly efficient self-trapped exciton (STE) broadband fluorescence emission, showing great potential in the field of luminescent materials. However, how to construct non-centrosymmetric crystal structures (to obtain strong NLO response) while maintaining high-efficiency photoluminescence in tin-based hybrid systems through rational molecular design, achieving a synergistic dual-function approach, remains a significant international frontier challenge.
[0006] Nitrogen-heterocyclic carbene (NHC), as a powerful ligand, possesses strong σ-electron-donating ability and tunable steric hindrance, and has shown great potential in the construction of functional coordination compounds and materials in recent years. NHC ligands not only stabilize metal centers, but their derived organic cations can also finely control the crystal's packing mode and overall symmetry through rich non-covalent interactions (such as hydrogen bonding, π-π stacking, and electrostatic interactions), thus profoundly affecting the macroscopic optoelectronic properties of materials. Using NHC derivative cations as structure-directing agents, combined with low-dimensional inorganic halide octahedrons, to control their configurational distortion is a promising but not yet fully explored approach for designing crystal materials with both nonlinear optical and unique luminescent properties.
[0007] From a methodological perspective, the traditional preparation of such functional crystals relies heavily on solution thermal methods, diffusion methods, or volatilization methods. These methods typically require large amounts of organic solvents, long reaction cycles, and precise temperature control, resulting in problems such as low efficiency, high energy consumption, severe environmental pollution, and poor reproducibility. Furthermore, it is difficult to precisely control the solvation effect during the crystallization process, leading to a degree of randomness in the regulation of crystal structure and properties.
[0008] Mechanochemistry is a green synthetic technique that directly induces physicochemical changes in solid materials through mechanical energy (such as grinding and ball milling). It enables efficient and rapid intermolecular contact and recombination under solvent-free or trace solvent conditions (liquid-phase grinding), providing new opportunities for synthesizing materials with novel structures and specific functions. In particular, mechanochemistry has unique advantages in exploring the synergistic regulation of crystal assembly by ligands and solvents, and holds promise for achieving precise and programmable control of crystal symmetry, nonlinear optics, and luminescence multifunctionality.
[0009] Based on the above background, this invention proposes an innovative solution: using the designed NHC derivative BMPIB as a unified organic structural unit, and employing a mechanochemical-assisted green synthesis strategy, a zero-dimensional tin halide single crystal material [BMPIB]·SnCl6 with a non-centrosymmetric structure, exhibiting strong second harmonic generation performance and efficient steady-state photoluminescence performance can be prepared efficiently and energy-savingly by precisely controlling the crystallization environment. Summary of the Invention
[0010] The primary objective of this invention is to overcome the conventional problems of environmental unfriendliness, low efficiency, and high cost associated with traditional synthesis methods, as well as the technical bottlenecks of rationally constructing non-centrosymmetric high-performance NLO crystals from tin-based hybrid materials and achieving efficient luminescence performance. The invention provides a novel bifunctional nitrogen-heterocyclic carbene-tin halide optical crystal material that combines strong second-harmonic generation performance with excellent photoluminescence characteristics. This material achieves a strong harmonic response through the non-centrosymmetric supramolecular assembly of organic cations and tin halide octahedra, synergistically endowing the material with efficient steady-state fluorescence emission, thereby realizing a dual-modal synergistic response of nonlinear optics and dynamic luminescence.
[0011] The second objective of this invention is to provide a green, efficient, simple, and reproducible mechanochemical preparation method for the aforementioned dual-functional optical crystal material that combines nonlinear optics and photoluminescence. This method is rapidly completed under near-solvent-free, room-temperature conditions, avoiding the use of expensive equipment or harsh conditions, and possesses the potential for large-scale production. Furthermore, it achieves precise control over crystal symmetry and the degree of distortion of the luminescence center through in-situ mechanically induced assembly.
[0012] The third objective of this invention is to elucidate the nonlinear optical properties and photoluminescence (fluorescence) properties of the crystal material and their physical mechanisms, and to provide application examples in the fields of laser frequency conversion devices, integrated optical chips, and advanced collaborative information encryption and anti-counterfeiting in static light emission-dynamic frequency doubling dual modes.
[0013] To achieve the above-mentioned objectives, the technical solution adopted by this invention is as follows:
[0014] Single-crystal material design scheme: 3-methyl-1-[(pyridin-2-yl)methyl]-1H-benzimidazole-3-onium chloride ([BMPIB]Cl), an NHC derivative with a rigid conjugated framework and multiple hydrogen bonding sites, is selected as the organic cation. This cation, through the NH and CH groups on its benzimidazole and pyridine rings, can react with inorganic [SnCl6]. 2- Octahedral anions form a widespread and oriented network of NH···Cl and CH···Cl hydrogen bonds. This strong, directional non-covalent interaction facilitates the crystal's assembly towards a non-centrosymmetric space group. Simultaneously, [BMPIB] 2+Its asymmetrical shape further reduces the probability of forming a centrosymmetric structure.
[0015] A bifunctional zero-dimensional organic-inorganic tin halide single-crystal material with nonlinear optics and strong fluorescence emission has the general chemical formula [BMPIB]·SnCl6. The basic structural unit of [BMPIB]·SnCl6 contains a discrete [SnCl6] crystal. 2- An octahedral anion and a [BMPIB] 2+ Organic cation, [SnCl6] 2- With [BMPIB] 2+ Three-dimensional supramolecular assemblies with double helix characteristics are formed by hydrogen bonding networks of NH···Cl and CH···Cl.
[0016] The above-mentioned method for preparing a bifunctional zero-dimensional organic-inorganic tin halide single crystal material with nonlinear optics and strong fluorescence emission includes the following steps:
[0017] 1) Synthesis of ligand [BMPIB]Cl: Using 2-chloromethylpyridine hydrochloride, N-methylbenzimidazole and inorganic base as raw materials, the reaction was carried out by mechanochemical reaction in a planetary ball mill under the condition of no external solvent. After filtration, washing and drying, a brown hygroscopic powder product [BMPIB]Cl was obtained.
[0018] 2) Synthesis of nonlinear optical crystal [BMPIB]·SnCl6: The [BMPIB]Cl obtained in step 1) and tin tetrachloride pentahydrate were placed together in a grinding container, and concentrated hydrochloric acid was added as a liquid-phase grinding aid and chlorine source supplement. The solid-solid reaction was carried out by mechanical grinding to obtain [BMPIB]·SnCl6 powder.
[0019] 3) Crystal growth and purification: The [BMPIB]·SnCl6 powder obtained in step 2) was dissolved in acetonitrile and recrystallized at 15-30℃ under light-proof and static conditions using a slow solvent evaporation method to precipitate pale yellow transparent blocky single crystals. After filtration, washing and drying, high-purity target nonlinear optical crystals were obtained.
[0020] Furthermore, in the above preparation method, in step 1), the inorganic base is sodium bicarbonate.
[0021] Furthermore, in the above preparation method, in step 1), the molar ratio of 2-chloromethylpyridine hydrochloride, N-methylbenzimidazole, and inorganic base is 1.0:1.1:1.5.
[0022] Furthermore, in the above preparation method, in step 1), the process conditions of the planetary ball mill are: a ball milling frequency of 30 Hz and a ball milling time of 1-2 hours.
[0023] Furthermore, in the above preparation method, in step 2), the molar ratio of [BMPIB]Cl to tin tetrachloride pentahydrate is 1:1.
[0024] Furthermore, in the above preparation method, step 2), the mechanical grinding is carried out using a vibratory ball mill with a vibration frequency of 30 Hz and a grinding time of 5 minutes.
[0025] Furthermore, in step 2) of the above preparation method, the amount of concentrated hydrochloric acid added is 30 μL of concentrated hydrochloric acid per 0.2 mmol of total reactants.
[0026] Furthermore, in the above preparation method, step 3), the slow solvent evaporation method is as follows: at 15-30℃, Parafilm is used to seal the bottle mouth, and the solvent evaporation rate is adjusted by controlling the container opening area and ambient humidity, and the container is left to stand for 3-7 days.
[0027] The above-mentioned dual-functional zero-dimensional organic-inorganic tin halide single crystal material with nonlinear optics and strong fluorescence emission is used in the preparation of dual-mode optical anti-counterfeiting labels, fluorescence-frequency doubling co-coding devices, multi-channel bioimaging probes, or integrated nonlinear photonics-light-emitting devices.
[0028] Compared with the prior art, the present invention has the following significant advantages and positive effects:
[0029] 1. Excellent crystal properties, with a unique dual-mode optical response:
[0030] The [BMPIB]·SnCl6 crystal provided by this invention has a defined non-centrosymmetric space group P212121. Under 1020 nm laser excitation, it generates a 510 nm second harmonic signal, and its powder frequency doubling (SHG) intensity reaches about 0.5 times that of Y-quartz, exhibiting a strong second-order nonlinear optical response.
[0031] This crystal exhibits excellent photoluminescence properties. Under ultraviolet light excitation, due to the strong exciton-phonon shuttle and self-trapped exciton (STE) emission mechanism of the zero-dimensional structure, the material exhibits efficient steady-state fluorescence emission, with a maximum emission peak at 440 nm and a phosphorescence lifetime of 22.4 ms.
[0032] This crystal has a wide optical bandgap (direct bandgap of about 4.03 eV), high thermal stability and good environmental stability, meeting the basic requirements for practical device applications.
[0033] 2. The synthesis method is green and efficient:
[0034] Environmentally friendly: The entire synthesis process from ligand to target crystal is carried out under solvent-free or trace solvent conditions, generating almost no organic waste liquid, eliminating volatile organic pollution at the source, and exhibiting high atom economy, which is in line with the principles of green chemistry and sustainable development.
[0035] High efficiency and energy saving: The mechanochemical reaction takes place at room temperature, requiring no external heating or cooling, resulting in extremely low energy consumption. Ligand synthesis and crystal precursor preparation are both completed within hours, significantly improving synthesis efficiency compared to traditional solution methods (which typically take days or even weeks).
[0036] Mild conditions and safe operation: No high temperature and high pressure, waterless and oxygen-free or inert atmosphere protection are required, which reduces equipment requirements and operational risks, and the process is highly safe.
[0037] 3. The process is simple and highly controllable:
[0038] The mechanochemical method used in this invention is simple to operate, requires little equipment (a ball mill or mortar and pestle is sufficient for laboratory use), has a concise process flow, and good reproducibility.
[0039] By adjusting the parameters of mechanical grinding (frequency, time, type and amount of grinding aid) and recrystallization conditions (solvent, temperature, evaporation rate), not only can the reaction degree of the precursor and the size and quality of the final crystal be effectively controlled, but also the distortion degree of the octahedral structure of inorganic metal halide [BMPIB]·SnCl6 and crystal defects can be finely adjusted, thereby achieving precise control of the steady-state fluorescence emission behavior and efficiency of the crystal, with high process flexibility.
[0040] 4. Low cost and easy to scale up:
[0041] The raw materials used (N-methylbenzimidazole, 2-chloromethylpyridine hydrochloride, SnCl6·H2O, etc.) are all commercially available and inexpensive chemicals. The mechanochemical method itself is easy to scale up from gram-level laboratory production to hundreds of grams or even kilogram-level production without complex modifications, and has broad prospects for industrialization.
[0042] 5. Wide range of applications:
[0043] Its optical second harmonic properties can be directly used to fabricate miniaturized laser frequency doubling devices, optical parametric oscillators and other nonlinear optical devices; its efficient light-emitting characteristics make it show important application potential in fields such as solid-state lighting and all-optical switching.
[0044] Because this material possesses a dual-modal optical response of "static UV-excited fluorescence color development" and "excitation frequency doubling response," and the two signals exhibit a high degree of independence and synergy in spatial and temporal scales, it has extremely high practical value in information security fields such as advanced dynamic optical anti-counterfeiting labels, multi-level all-optical information encryption and decryption, and anti-counterfeiting traceability, which is unmatched by traditional single-function materials.
[0045] 6. Significant scientific significance:
[0046] This invention not only provides a high-performance nonlinear optical-photoluminescence bifunctional hybrid crystal material, but more importantly, it demonstrates a universal strategy for the green preparation of noncentrosymmetric multifunctional crystals by combining "ligand engineering" with "mechanical chemical synthesis". Attached Figure Description
[0047] Figure 1 The proton nuclear magnetic resonance spectrum of [BMPIB]Cl synthesized in Example 1 of this invention ( 1 (H NMR) image.
[0048] Figure 2 The images shown are photographs of the product obtained in Example 2 of the present invention, wherein: (a) is a diagram of the grinding powder crystal state of the crude [BMPIB]·SnCl6 product; (b) is a diagram of the recrystallization process of the [BMPIB]·SnCl6 solution volatilization method; Figure 2 (c) is a microscopic morphology diagram of the single crystal obtained after recrystallization of [BMPIB]·SnCl6.
[0049] Figure 3 X-ray powder diffraction (PXRD) of [BMPIB]·SnCl6 powder crystals and their recrystallization products obtained by mechanical grinding in Example 3 of the present invention.
[0050] Figure 4 This is the crystal structure diagram of [BMPIB]·SnCl6.
[0051] Figure 5 The image shows a comparison of the second harmonic generation signal intensity of [BMPIB]·SnCl6 (black curve) measured by the Kurtz-Perry powder method and the reference Y-quartz (red curve) under 1020 nm laser pumping.
[0052] Figure 6 The UV-Vis diffuse reflectance spectrum of [BMPIB]·SnCl6 crystal and the resulting Tauc plot.
[0053] Figure 7 Thermogravimetric analysis (TGA) curves of [BMPIB]·SnCl6 crystals.
[0054] Figure 8Afterglow decay images of [BMPIB]·SnCl6 powder prepared in Example 2 of this invention after the 365 nm UV lamp was turned off (time intervals: 0.1 s, 0.2 s, 0.3 s, 0.6 s, 1.0 s, 1.2 s, 1.4 s).
[0055] Figure 9 The images show the steady-state photoluminescence (PL) spectrum and photoluminescence excitation (PLE) spectrum of the [BMPIB]·SnCl6 powder crystals prepared in Example 2 of this invention at room temperature.
[0056] Figure 10 This is a transient fluorescence lifetime decay curve of the [BMPIB]·SnCl6 powder prepared in Example 2 of the present invention at room temperature.
[0057] Figure 11 This invention relates to the anti-counterfeiting application of [BMPIB]·SnCl6 powder prepared in Example 2 of the present invention in QR code recognition. Detailed Implementation
[0058] Example 1: Mechanochemical Synthesis of Ligand [BMPIB]Cl
[0059] 2-(chloromethyl)pyridine hydrochloride (6.28 mg), N-methylbenzimidazole (5.57 mg), and sodium bicarbonate (4.82 mg) were added to a 25 mL zirconia ball mill jar and ball-milled at 30 Hz for 1.5 h under completely solvent-free conditions (or with 1-2 mL of methanol as an auxiliary liquid). After the reaction was complete, insoluble inorganic salts were removed by filtration, and the filtrate was washed with ethyl acetate (30 mL × 3). The organic phase was dried over anhydrous Na₂SO₄ and filtered through diatomaceous earth. The solvent was then evaporated again to give a reddish-brown oily liquid. The product was stirred with diethyl ether (15 mL) under cooling conditions, filtered, and dried. A brown hygroscopic powder was finally obtained in 81% yield.
[0060] By nuclear magnetic resonance hydrogen spectrum ( 1 The structure of the product was confirmed by H NMR (400 MHz, DMSO-d6) (see [link to H NMR]). Figure 1 The spectrum matches the target structure.
[0061] Example 2: Mechanochemical preparation and crystal growth of the nonlinear optical crystal [BMPIB]·SnCl6
[0062] Mechanochemical synthesis: Accurately weigh the [BMPIB]Cl ligand (26.0 mg, 0.10 mmol) synthesized in Example 1 and tin tetrachloride pentahydrate (SnCl4·5H2O, 35.1 mg, 0.10 mmol), and place them together in a 25 mL zirconia ball mill jar. Add a 16 mm diameter zirconia grinding ball to the jar. Accurately measure 30 μL of concentrated hydrochloric acid (37 wt%) using a microsyringe and drop it onto the surface of the solid mixture. Quickly seal the ball mill jar and mount it on the clamp of a vibratory ball mill (model: MM 400, Retsch GmbH, Germany). Set the ball mill operating parameters to: vibration frequency 30 Hz, grinding time 5 minutes. Start the ball mill; a distinct grinding sound can be heard during the reaction. After grinding, open the ball mill jar to obtain a light yellow, uniform, fine powder.
[0063] Single crystal cultivation: Carefully transfer the ground powder obtained above into a 20 mL transparent glass sample vial. Add 4 mL of acetonitrile, a polar, protically inert solvent, to the vial, and gently shake or use sonication to completely dissolve the powder, obtaining a clear, colorless solution. Use parafilm to poke 4-6 small holes at the vial opening to control the solvent evaporation rate. After standing for 3 days, a large amount of pale yellow, transparent, blocky single crystals with regular geometric shapes (such as...) will gradually precipitate at the bottom and walls of the vial. Figure 2 Larger, well-formed crystals were carefully picked up with tweezers. The crystal surface was quickly rinsed with a small amount of cold acetonitrile (approximately 0.5 mL) to remove adsorbed mother liquor. The crystals were then blotted dry on filter paper and transferred to a petri dish to air dry at room temperature for 2 hours. Approximately 35 mg of high-quality single crystals were finally obtained (yield approximately 78% based on Sn calculations). The melting point of the crystals was determined to be 228.2–230.6°C using a capillary method.
[0064] Example 3 Structural characterization of the nonlinear optical crystal [BMPIB]·SnCl6 crystal
[0065] Powder diffraction test: Small amounts of the [BMPIB]·SnCl6 powder crystals prepared by grinding and the crystal products obtained by recrystallization were respectively subjected to X-ray powder diffraction (PXRD) tests, and the spectra were obtained. Figure 3 ) and from subsequent single-crystal structures ( Figure 4 The simulated powder diffraction pattern is completely consistent with that of the grinding product, indicating that the grinding product has the correct phase.
[0066] Single crystal structure analysis: A single crystal with dimensions of approximately 0.15 × 0.10 × 0.08 mm was selected from Example 2. 3Bulk single crystals were obtained, and data were collected at room temperature using Mo Kα rays (λ = 0.71073 Å) on a Bruker D8 Quest single-crystal diffractometer. Data reduction was performed using the SAINT program, and absorption correction was performed using the SADABS program. The crystal structure was resolved using the direct method (SHELXT) and refined using the full matrix least squares method (SHELXL). All non-hydrogen atoms were refined using anisotropic thermal parameters, and hydrogen atoms on organic ligands were added using a rider-shoot model.
[0067] Structure confirmed: The crystal belongs to the orthorhombic crystal system, space group P212121 (International Crystallographic Table No. 19), which is a non-centrosymmetric space group. The Flack parameter was refined to -0.019(5), further confirming that the crystal is an enantiomeric non-centrosymmetric structure. The cell parameters are: a = 10.523(2) Å, b = 12.847(3) Å, c = 14.296(3) Å. V = 1932.1(7)Å 3 , Z = 4. The asymmetric unit contains a discrete [SnCl6] 2- An octahedral anion and an independent [BMPIB] 2+ cation( Figure 4 [SnCl6] 2- The octahedrons interact with the surrounding organic cations through abundant NH···Cl and CH···Cl hydrogen bonds (bond length range: 2.9–3.8 Å). This helical assembly driven by directional hydrogen bonds is a key factor leading to the loss of the crystal's center of symmetry. The main Sn—Cl bond lengths and Cl—Sn—Cl bond angles are shown in Table 1.
[0068] Table 1. Sn—Cl bond length and Cl—Sn—Cl bond angle data
[0069]
[0070] Example 4: Nonlinear Optical Performance Testing
[0071] Second Harmonic Generation (SHG) Performance Testing: The SHG strength of the crystals was tested using the standard Kurtz-Perry powder method. A portion of the crystals obtained in Example 2 was carefully ground in an agate mortar and sieved to obtain powder with a particle size range of 150-200 μm. The powder was uniformly and tightly filled into a sample groove between two circular glass slides to create a flat sample sheet with a thickness of approximately 1 mm. Y-quartz powder with a uniform particle size was prepared using the same method as a reference sample.
[0072] A Q-switched Nd:YAG pulsed laser (wavelength 1020 nm, pulse width 10 ns, repetition rate 10 Hz) was used as the pump source. The laser beam, after its energy was adjusted by an attenuator, was incident perpendicularly onto the sample surface. The frequency-doubled light (510 nm) generated by the sample was filtered (to remove the 1020 nm fundamental frequency light), received by a photomultiplier tube (PMT), and converted into an electrical signal. The signal intensity was then recorded using a digital oscilloscope. A precision translation stage was used to move the sample, ensuring that the laser spot size and position were consistent for each test.
[0073] Under the same pump energy density (20 mJ / pulse), the SHG signal intensity of the [BMPIB]·SnCl6 sample and the γ-quartz reference sample were measured respectively. After multiple measurements and averaging, the SHG intensity of the [BMPIB]·SnCl6 powder was calculated to be approximately 0.5 times that of the γ-quartz sample. Figure 5 It exhibits excellent second-harmonic nonlinear optical performance.
[0074] UV-Vis spectroscopy: The diffuse reflectance spectrum of [BMPIB]·SnCl6 powder was measured using a UV-Vis spectrophotometer equipped with an integrating sphere. The spectrum was converted using the Kubelka-Munk function and a Tauc plot was plotted (αhν). 2 Compared to hν, extrapolation yields a direct optical bandgap of approximately 4.03 eV. Figure 6 This indicates that the material is a wide-bandgap semiconductor, transparent in the visible light region, which is beneficial for nonlinear optical applications.
[0075] Example 5 Stability Characterization
[0076] Thermogravimetric analysis (TGA) of the crystalline powder was performed under a nitrogen atmosphere at a heating rate of 10°C / min. The results showed that ( Figure 7 The material exhibits excellent thermal stability, showing no significant weight loss before 240°C. The main decomposition process occurs above 240°C.
[0077] Example 6: Second-level room temperature phosphorescence properties and photoluminescence (PL) and photoluminescence excitation (PLE) spectra measurements
[0078] The crystal obtained in Example 2 was irradiated under a 365 nm ultraviolet lamp for 30 seconds, and then the light source was turned off. The afterglow decay process was recorded using a digital camera. Figure 8 The results showed that the crystal continued to emit blue visible light even after the ultraviolet lamp was turned off, and the afterglow was visible to the naked eye for more than 1.4 seconds, further confirming that the material has excellent long-life room temperature phosphorescence properties.
[0079] The excitation spectrum (PLE) shows a maximum peak at 366 nm, while the emission spectrum (PL) exhibits a broadband emission peak with a maximum emission wavelength at 440 nm, displaying the characteristic self-trapped exciton (STE) luminescence features unique to zero-dimensional hybrid metal halides. Figure 9 The transient fluorescence lifetime decay curve at room temperature was fitted with an exponential function, and the goodness of fit R for this crystal was [value missing]. 2 The phosphorescence efficiency reached 0.993, with an average phosphorescence lifetime of 22.4 ms. Figure 10 ).
[0080] Example 7: Application of the prepared [BMPIB]·SnCl6 powder in QR code recognition anti-counterfeiting.
[0081] [BMPIB]·SnCl6 microcrystalline powder changed from yellow to white under 365 nm ultraviolet light excitation, indicating an initial static pattern. Figure 11 After 0.6 seconds, a yellow afterglow further appeared, clearly displaying the QR code.
Claims
1. A bifunctional zero-dimensional organic-inorganic tin halide single crystal material with nonlinear optics and strong fluorescence emission, characterized in that, The single-crystal material has the general chemical formula [BMPIB]·SnCl6, and the basic structural unit of [BMPIB]·SnCl6 contains a discrete [SnCl6] atom. 2- An octahedral anion and a [BMPIB] 2+ Organic cation, [SnCl6] 2- With [BMPIB] 2+ Three-dimensional supramolecular assemblies with double helix characteristics are formed by hydrogen bonding networks of NH···Cl and CH···Cl.
2. The method for preparing a bifunctional zero-dimensional organic-inorganic tin halide single crystal material with nonlinear optics and strong fluorescence emission as described in claim 1, characterized in that, Includes the following steps: 1) Synthesis of ligand [BMPIB]Cl: Using 2-chloromethylpyridine hydrochloride, N-methylbenzimidazole and inorganic base as raw materials, the reaction was carried out by mechanochemical reaction in a planetary ball mill under the condition of no external solvent. After filtration, washing and drying, a brown hygroscopic powder product [BMPIB]Cl was obtained. 2) Synthesis of nonlinear optical crystal [BMPIB]·SnCl6: The [BMPIB]Cl obtained in step 1) and tin tetrachloride pentahydrate were placed together in a grinding container, and concentrated hydrochloric acid was added as a liquid-phase grinding aid and chlorine source supplement. The solid-solid reaction was carried out by mechanical grinding to obtain [BMPIB]·SnCl6 powder. 3) Crystal growth and purification: The [BMPIB]·SnCl6 powder obtained in step 2) was dissolved in acetonitrile and recrystallized at 15-30℃ under light-proof and static conditions using a slow solvent evaporation method to precipitate pale yellow transparent blocky single crystals. After filtration, washing and drying, high-purity target nonlinear optical crystals were obtained.
3. The preparation method according to claim 2, characterized in that, In step 1), the inorganic base is sodium bicarbonate.
4. The preparation method according to claim 2, characterized in that, In step 1), the molar ratio of 2-chloromethylpyridine hydrochloride, N-methylbenzimidazole and inorganic base is 1.0:1.1:1.
5.
5. The preparation method according to claim 2, characterized in that, In step 1), the process conditions of the planetary ball mill are: a ball milling frequency of 30 Hz and a ball milling time of 1-2 hours.
6. The preparation method according to claim 2, characterized in that, In step 2), the molar ratio of [BMPIB]Cl to tin tetrachloride pentahydrate is 1:
1.
7. The preparation method according to claim 2, characterized in that, In step 2), the mechanical grinding is carried out using a vibratory ball mill with a vibration frequency of 30 Hz and a grinding time of 5 minutes.
8. The preparation method according to claim 2, characterized in that, In step 2), the amount of concentrated hydrochloric acid added is 30 μL of concentrated hydrochloric acid per 0.2 mmol of total reactants.
9. The preparation method according to claim 2, characterized in that, In step 3), the slow solvent evaporation method is as follows: at 15-30℃, Parafilm is used to seal the bottle mouth, and the solvent evaporation rate is adjusted by controlling the container opening area and ambient humidity, and the container is left to stand for 3-7 days.
10. The application of the bifunctional zero-dimensional organic-inorganic tin halide single crystal material with nonlinear optics and strong fluorescence emission as described in claim 1 in the preparation of dual-mode optical anti-counterfeiting labels, fluorescence-frequency doubling co-coding devices, multi-channel bioimaging probes, or integrated nonlinear photonics-light-emitting devices.
